FILOLOGI NASKAH TAFSÎR BI AL-IMLÂ’ SURAT AL-BAQARAH KARYA KYAI ZAINI MUN’IM - Fawaid, Ahmad (Jurnal Studi Ilmu-ilmu Al-Qur’an dan Hadis, 2019)
This is a philological study of the manuscript tafsîr bi al-Imlâ’ surat al-Baqarah Kyai Zaini Mun’im, the first founder of Nurul Jadid Islamic Boarding School Paiton, Probolinggo. This study deals to discuss systematic, forms, methods, style and ideology that contained in the script of tafsîr bi al-imlâ’ surat al-Baqarah. Having studied manuscript of tafsîr bi al-Imlâ’, it can be identified that: commentaries (tafsîr) of Kyai Zaini used tartib muṣḥafî’s systematic presentation, ra’yî’s form, taḥlîlî’s method, adabî ijtima’î’s style and Ahl al-Sunnah wa al-Jama’ah’s ideology. In addition, this study also found that the interpretation bi al-imlâ’ many affected by tafsîr al-Marâghî of Shaikh al-Marâghî and al-Manâr by Shaikh Muhammad Abduh and Rasyid Rida, in the form of ideas and writing formats. Nevertheless, in some interpretation on certain verses, Kyai Zaini’s interpretation is partly different from the two interpretation above, and it becomes its own peculiarities of the intellectual work of islamic boarding school.